Designing the Process for Disassembling Car Wheels using Industrial Robot Collaborated with Virtual Reality Technology - Trakunsaranakom, Channarong (Princess of Naradhiwas University Journal, 2021)
This research aims to design the process for disassembling car wheels using industrial robot collaborated with virtual reality technology through robot applications. The modular structured and procedural programming use a high-level robotic language programming. This research proposes methods for robot arm movement and industrial robot positioning in work cell simulation by developing an integrated program. The design in this process involves in removing the screws from the wheel of the car and putting it in the right place. The operation begins with whether the inspection of the block wrench attached to the robot arm correctly, and if using the wrong wrench, the robot program will change the correct wrench before screwing it. The screwing out and placing screws of car wheels in 5 correct positions were tested. The experiment evaluated the accuracy of the robot arm in identifying in a virtual reality environment. The process compared between the stereo virtual environment and the virtual device environment. The equipment used in the experiment consisted of 3D glasses and virtual control devices. From the experiment, it can be seen that the stereo virtual environments were more accurate than virtual device environments. The process design can be used for planning work in industrial automation. A good process design will allow the machine to work systematically with high accuracy which helps saving time and creating a competitive advantage.